Determinan Profitabilitas Sektor Perusahaan Perbankan Dengan CAR Sebagai Variabel Mediasi - Sinta, Adinda Dhea Tiara; Rachmawati, Nurul Aisyah (Unversitas Islam Madura, 2025)
Return on Equity (ROE) is a ratio that measures bank management's ability to manage its capital to produce net profit after tax. The higher the Return on Equity (ROE), the better the bank's performance. To predict the expected ROE, this research uses Loan To Deposit Ratio (LDR), Non Performing Loan (NPL), Operational Costs to Operating Income (BOPO), and the mediating variable Capital Adequacy Ratio (CAR). This research uses panel data regression analysis techniques in the banking company sector listed on the IDX for the 2018-2022 period. The results of this research show that there are three variables that have a direct and significant effect on ROE, namely LDR, BOPO, and CAR. The results of this research also show that CAR can mediate the influence of LDR and BOPO on ROE.